9. THE ROLE OF EOS IMAGING SYSTEM TO EVALUATE MAXIMAL AXIAL VERTEBRA ROTATION IN ADOLESCENT IDIOPATHIC SCOLIOSIS (Vietnam Journal of Community Medicine, 2024)
Background: Neglecting or misunderstanding the assessment of vertebral rotation can lead to inaccuracies during surgery. However, no assessment of vertebral rotation is totally reliable.Purposes: This study evaluated the relationship between maximal axial vertebra rotation (maxAVR) and other clinical and radiological indexes, compared to apical vertebra rotation (AVR) in idiopathic adolescent scoliosis (AIS).Methods: Forty consecutive patients of AIS with Cobb angle of major curve > 40° were included. They were scanned by an EOS imaging system and had trunk rotational angle (TRA) measured by scoliometer. The correlation between variables was assessed using Pearson’s correlation coefficient and loaded onto a meta-analysis model.Results: There were (34 girls and 6 boys) with an average age of 13.8±1.6 years. AVR was maxAVR in only 47.5% (19/40) cases of the major curves and 42.3% (11/26) cases of the minor curves. The correlation between maxAVR and TRA was significantly higher than the correlation between AVR and TRA for the MT curves (p=0.0001) and TL/L curves (p=0.0001). On multivariate regression analysis, the magnitude of maxAVR showed a significant correlation with TRA (p=0.0002), Cobb angle (p=0.001), and coronal deformity angular ratio (C-DAR) (p=0.027).Conclusions: The apical vertebra was not the most rotated in most cases. The correlation between maxAVR and TRA was significantly higher than the correlation between AVR and TRA. Moreover, the maxAVR was multivariately related to TRA, Cobb angle, and C-DAR.
Keywords: Trunk rotational angle; Apical vertebral rotation; Maximal axial vertebral rotation; Coronal deformity angular ratio